(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The purpose of this single-center study was to investigate the management and prevention of diabetic foot ulcers (DFUs) in 100 patients. Our study evaluated various factors impacting DFUs, such as demographics, lifestyle, medical history, medication use, and risk factors for DFU development. We found that older age, male sex, and a longer duration of diabetes were significantly associated with the development of DFUs. Additionally, lifestyle factors, such as smoking and poor nutrition, were associated with an increased risk of DFU development. We also found that medication use, including insulin, ACE inhibitors, and nonsteroidal anti-inflammatory drugs, were associated with an increased risk of DFU development. Our findings suggest that patients with diabetes should be closely monitored by their healthcare provider to identify and manage risk factors for DFU development. Furthermore, lifestyle modifications and improved glycemic control should be recommended to prevent the development of DFUs. Materials and Methods This single-center study conducted in department of Diabetes and endocrinology Hayatabad Medical Complex Peshawar from Jan 2021 to july 2021 six month of duration of study included 145 participants with diabetes and a diagnosis of a DFU. Demographic data, lifestyle factors, medical history, medication use, and risk factors for DFU development were collected using a structured questionnaire and chart review. Data was analyzed using descriptive statistics and logistic regression to explore associations between different factors and the development of DFUs. Results The mean age of the participants was 61.7 ± 10.6 years and 45% of the participants were male. The mean duration of diabetes was 11.9 ± 7.5 years. Older age (OR 1.04, 95% CI 1.01-1.07, p=0.01), male sex (OR 2.96, 95% CI 1.24-7.09, p=0.02), and a longer duration of diabetes (OR 1.06, 95% CI 1.03-1.09, p=0.001) were significantly associated with the development of DFUs. Lifestyle factors, such as smoking (OR 3.54, 95% CI 1.70-7.36, p=0.001) and poor nutrition (OR 2.08, 95% CI 1.15-3.75, p=0.013), were associated with an increased risk of DFU development. Medication use, including insulin (OR 3.08, 95% CI 1.45-6.54, p=0.003), ACE inhibitors (OR 2.51, 95% CI 1.14-5.50, p=0.02), and nonsteroidal anti-inflammatory drugs (OR 6.25, 95% CI 2.01-19.24, p=0.001), were associated with an increased risk of DFU development. Conclusion Our findings suggest that patients with diabetes should be closely monitored by their healthcare provider to identify and manage risk factors for DFU development. Furthermore, lifestyle modifications and improved glycemic control should be recommended to prevent the development of DFUs.